Penggunaan Media Puzzle dalam Meningkatkan Kemampuan Mengenal Angka 1-10 Pada Siswa Tunagrahita Ringan di Kelas 1 SLB Maranatha Airmadidi - Sidik Ngurawan (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of the study was to obtain data, analyze and interpret numbers using number puzzle media for first graders at SLB GMIM Maranatha Airmadidi. This research method is quantitative in the form of Single Subject Research (SSR). Observation and test data collection techniques. Data processing techniques were analyzed quantitatively. The data were analyzed using visual graph analysis (visual of data graph analysis), namely by plotting the data into graphs, then the data was analyzed based on the components in each condition (A and B). analysis was carried out under conditions and between conditions. Research results: Based on the results of data analysis, it is proven that the ability to recognize numbers 1-10 children with mild mental retardation in class I at SLB GMIM Maranatha Airmadidi. especially in solving problems as many as 20 questions can be improved by using Puzzle media.